REPRODUCTION AND DEVELOPMENT OF BEES - Murodova Hilola Zafarjon qizi (Journals Park Publishing, 2022)
Bees belong to the class of insects and live as a family. Their reproduction and development are varied and complex, including sexual reproduction and parthenogenesis. It is fully developed and multiplies to form a fungus. This article discusses the reproduction and development of bees, ways of artificial    technologies for their reproduction will be covered.
Keywords: mother bee; male bee (drones); worker bee